Simplify the function..........
1 answer:
7ab a - b
-------------- - --------------
a^2 - b^2 a + b
7ab a - b
= -------------- - --------------
(a-b)(a+b) a + b
7ab (a - b)^2
= -------------- - -----------------------
(a-b)(a+b) (a + b)(a-b)
7ab a^2 - 2ab + b^2
= -------------- - -----------------------
(a-b)(a+b) (a + b)(a-b)
7ab - a^2 + 2ab - b^2
= -----------------------------------
(a-b)(a+b)
- a^2 + 9ab - b^2
= -----------------------------------
(a-b)(a+b)
Answer is A. first one
You might be interested in
The answer is -0.8 welcome
225000=200000(1.03^t)
9/8=1.03^t
ln(9/8)=tln(1.03)
t=ln(9/8)/ln(1.03)
t=3.98
t=4 years
Answer:i believe it is the first answer
Step-by-step explanation:
I’m a little confused do you have a picture I could solve for cos then